Structural and electrical properties of ZnO varistors containing different spinel phases - Brankovic, Z.; Brankovic, G.; Poleti, D.; Varela, José Arana [UNESP] (Elsevier B.V., 2001)
Structural and electrical properties of ZnO varistors were investigated as a function of spinel composition. Six varistor mixtures differing only in chemical composition of spinel, were prepared by mixing separately synthesized constituent phases (DSCP method). Compositions of constituent phases in sintered samples were investigated by changes of lattice parameters of the phases, as well as by EDS analysis of the constituent phases. It was found that compositions of ZnO, intergranular and spinel phases were partially changed during sintering due to redistribution of additives, that was controlled by starting spinel composition and its stability. Electrical characterization showed significant difference in electrical properties of investigated varistors: nonlinearity coefficients ranging from 22 to 55 and leakage currents differing by the order of magnitude. Activation energies of conduction were obtained from ac impedance spectroscopy measurements. Calculated values of activation energies were in the range 0.61-1.0 eV confirming difference in defect structure of ZnO grain boundaries in varistors containing different spinel phases. (C) 2001 Elsevier B.V. Ltd and Techna S.r.l. All rights reserved.
Keywords: X-ray method; electrical properties; spinels; varistors